FAKTOR – FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN : PERAN MODERASI GOOD CORPORATE GOVERNANCE : DETERMINANTS OF THE FIRM VALUE: THE MODERATION ROLE OF GOOD CORPORATE GOVERNANCE (EMPIRICAL STUDY ON ISLAMIC COMMERCIAL BANKS IN 2015 - 2020) - Herwika, Essi; Anugerah, Rita; Nurmayanti, Poppy (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This study aims to examine and analyze the effect of intellectual capital, managerial ownership, and risk management on firm value moderated by good corporate governance at Islamic Commercial Banks in Indonesia from 2015 to 2020 and differences in the effect of IC, managerial ownership, and risk management on firm value in Government-owned and Privately-owned Islamic Commercial Banks in Indonesia from 2015 to 2020. The population in this study amounted to 14 Islamic commercial banks with a sample of 12 banks. The data analysis used in this research is Multiple Linear Regression, Moderate Regression Analysis, sensitivity analysis and regression coefficient test.The result of research shows that intellectual capital affects the value of Islamic Commercial Bank companies. This means that the better the intellectual capital, the more the company value will increase. Managerial ownership has no significant effect on the value of Islamic Commercial Bank companies. Risk management has a significant positif effect on the value of Islamic Commercial Bank companies. GCG moderates the effect of intellectual capital and risk management on the value of Islamic Commercial Bank companies, but does not moderate managerial ownership.